Makrotętniak odgałęzienia tętnicy środkowej siatkówki - Gawęcki, Maciej; Raczyńska, Krystyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Authors present review of modern diagnostic and therapeutic methods in dealing with retinal macroaneurysms, illustrated by own case reports. The key diagnostic test for retinal macroaneurysms is fluorescein angiography. Prognosis for preserving vision depends on the character of retinal macroaneurysm complications such as hard exudates and haemorrhages after macroaneurysm rupture and its localization in regard to the macular area. Treatment options are related to severity of subjective symptoms and can be conservative or surgical.